Application of manganese-containing soil as novel catalyst for low-temperature NH3-SCR of NO. Issue 4 (August 2021) - Wu, Hongli; He, Minyu; Liu, Weizao; Jiang, Lijun; Cao, Jun; Yang, Chen; Yang, Jie; Peng, Jing; Liu, Yi; Liu, Qingcai
Abstract: Manganese-containing soil (M-S) is a solid waste generated from the mining and extraction of manganese ore. In this study, the low-temperature denitration performance of Mn-S was investigated via XRF, XRD, XPS, H2 -TPR, NH3 -TPD and DRIFTS, aiming at exploring its utilization approach as low-temperature NH3 -SCR catalyst. The results showed that Mn-S exhibited a relatively high catalytic activity reaching over 75% NO conversion from 150 °C to 200 °C. The physical and chemical properties of Mn-S were studied, indicating that the manganese content of Mn-S reached 8.2% with mainly surface Mn atomic valence state of Mn 3+ . In situ DRIFTS results revealed the SCR reaction mechanism of Mn-S, suggesting that Mn-S obeyed the E-R reaction mechanism. The Ce/Mn-S catalyst was synthesized by impregnation method. The denitration activity improved and reached 92.4% at 200 °C. A series of characterizations were studied to investigate the strengthening mechanism after doping Ce. It's found that introducing of Ce could increase the content of Mn 4+ and chemisorbed oxygen, NH3 adsorption capacity and reducibility. It was found from in situ DRIFTS experiments that doping of Ce changed the reaction mechanism due to the conversion of inactive substance, which was mainly affected by E-R and L-H. Graphical Abstract: ga1 Highlights: The excellent low-temperature denitration performance of Mn-S was investigated. Ce-dropped Ce/Mn-S catalyst exhibited high denitration performance and improved N2 selectivity. Doping Ce enhanced the content of Mn 4+ and chemisorbed oxygen. Supporting Ce changed the SCR reaction mechanism due to the conversion of inactive substance.